Negotiating the Indian Ocean Whale Sanctuary - Holt, Sidney (J. Cetacean Res. Manage., 2023)
This paper provides an overview of the establishment of the International Whaling Commission’s Indian Ocean Sanctuary in 1979. The International Convention for the Regulation of Whaling enables the IWC to designate sanctuaries as well as open and closed areas for whaling. The author reflects upon the background to the issue of whale sanctuaries within the IWC and the particular role of the Seychelles Government in the development of the proposal for a sanctuary in the Indian Ocean. He notes the political, scientific and practical factors surrounding the acceptance of the proposal by the IWC and briefly discusses subsequent events.